2016
DOI: 10.1039/c5cy01012h
|View full text |Cite
|
Sign up to set email alerts
|

Silica-supported metal acetylacetonate catalysts with a robust and flexible linker constructed by using 2-butoxy-3,4-dihydropyrans as dual anchoring reagents and ligand donors

Abstract: 2-Butoxy-3,4-dihydropyrans were used, for the first time, as dual anchoring reagents and ligand donors to prepare the immobilize homogeneous metal acetylacetonate catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 88 publications
(15 reference statements)
1
32
0
Order By: Relevance
“…To address this issue, several research groups have reported catalytic systems facilitating both homo‐ as well as hetero‐coupling reactions of alkynes. Copper catalysts in comparison to other metals have shown promising results at elevated temperature as reported by Lei et al., Suib et al., and several others . Room temperature protocols by Cai et al., Yao et al .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To address this issue, several research groups have reported catalytic systems facilitating both homo‐ as well as hetero‐coupling reactions of alkynes. Copper catalysts in comparison to other metals have shown promising results at elevated temperature as reported by Lei et al., Suib et al., and several others . Room temperature protocols by Cai et al., Yao et al .…”
Section: Introductionmentioning
confidence: 89%
“…Copper catalysts in comparison to other metals have shown promising results at elevated temperature as reported by Lei et al, [13] Suib et al, [14] and several others. [15][16][17] Room temperature protocols by Cai et al, [18] Yao et al [19] and Hwang et al [20] further emphasized the persisting interest in such alkyne hetero-couplings. A closer inspection of these reports, however, suggests that the applied conditions are most often not suitable for reacting molecules withlabile functional groups or important biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these systems are usually homogeneous and suffer from inherent drawbacks: difficulty in separating the catalyst and product, environmental concern, and recyclability. Recent research in this area has focused on beneficial heterogeneous catalysis which can address these problems and has several advantages such as easier separation of catalyst and product(s), better recovery, allowing for reuse of the catalyst systems, and reduced metal contamination in the final products . In this context, magnetic nanoparticles (MNPs) are considered promising catalysts because of their response to an external magnetic field and are thus extensively used in a variety of important organic reactions .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of their strong hydrophobicity, the recovery and reuse of these catalysts relies heavily on modern immobilization technologies by using either silica or ionic liquids as supports . Recently, we developed a new method for the preparation of silica‐supported metal acetylacetonate catalysts by using 2‐alkoxy‐3,4‐dihydropyrans as dual anchoring reagents and ligand donors . In our method, we installed a robust and flexible linker through a ring‐opening reaction of the dihydropyran with thiol‐functionalized silica and used it to tether the metal complex.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recently,w ed eveloped a new method for the preparation of silica-supported metal acetylacetonate catalysts by using 2-alkoxy-3,4-dihydropyrans as dual anchoring reagents and ligand donors. [14] In our method, we installed ar obust and flexible linker through ar ing-opening reactiono ft he dihydropyran with thiol-functionalized silica and used it to tether the metal complex. The thus-obtained solid catalystd isplayed quite-remarkable performance in some organic reactions.…”
Section: Introductionmentioning
confidence: 99%